Assessment of dentists' behaviour on the use of patients' images. (23rd May 2020) - Costa, Eliana Dantas; Martins, Luciano Augusto Cano; Cral, Wilson Gustavo; Peroni, Leonardo Vieira; Freitas, Deborah Queiroz; Oliveira, Matheus Lima
Abstract: Background: Photographs and radiographs are indispensable resources for dental education, research and dissemination of clinical cases in scientific journals. The objective of this study was to evaluate the behaviour of dentists on the use of patients' images. Material and Methods: Fifty‐two dentists were interviewed using a semi‐structured script containing open‐ended questions on the use of patients' images. The answers were analysed using a qualitative‐quantitative method of the discourse of the collective subject, and the distribution of the absolute and relative frequency of the answers was presented according to the central ideas obtained from the discourses. Results: The following central ideas on the use of patients' images were identified: (a) purpose: didactic and/or academic; (b) informed consent: verbal or absent when the patient cannot be identified; (c) discussion groups on social media contribute to learning; (d) most dentists would not appreciate and sue the author if they had their own photographs/imaging examinations posted on social media; 5. most dentists received some information on ethical regulations during dental school and state that images can be used with patient authorisation, without identification and for didactic/academic purposes. Conclusion: Dentists consider the use of patients' images for didactic and scientific purposes beneficial, request informed consent to share mainly images that reveal the identity and would not appreciate if their personal images were shared without consent.